Cytotoxicity and molecular docking analysis of racemolactone I, a new sesquiterpene lactone isolated from Inula racemosa. (1st January 2021) - Alam, Perwez; Tyagi, Rama; Farah, Mohammad Abul; Rehman, Md. Tabish; Hussain, Afzal; AlAjmi, Mohamed Fahad; Siddiqui, Nasir Ali; Al-Anazi, Khalid Mashay; Amin, Saima; Mujeeb, Mohd.; Mir, Showkat R.
Abstract: Context: Traditionally, Inula racemosa Hook. f. (Asteraceae) has been reported to be effective in cancer treatment which motivated the authors to explore the plant for novel anticancer compounds. Objective: To isolate and characterize new cytotoxic phytoconstituents from I. racemosa roots. Materials and methods: The column chromatography of I. racemosa ethyl acetate extract furnished a novel sesquiterpene lactone whose structure was established by NMR (1D/2D), ES-MS and its cytotoxic properties were assessed on HeLa, MDAMB-231, and A549 cell lines using MTT and LDH (lactate dehydrogenase) assays. Further, morphological changes were analyzed by flow cytometry, mitochondrial membrane potential, AO-EtBr dual staining, and comet assay. Molecular docking and simulation were performed using Glide and Desmond softwares, respectively, to validate the mechanism of action. Results: The isolated compound was identified as racemolactone I (compound 1 ). Amongst the cell lines tested, considerable changes were observed in HeLa cells. Compound 1 (IC50 = 0.9 µg/mL) significantly decreased cell viability (82%) concomitantly with high LDH release (76%) at 15 µg/mL. Diverse morphological alterations along with significant increase (9.23%) in apoptotic cells and decrease in viable cells were observed. AO-EtBr dual staining also confirmed the presence of 20% apoptotic cells. A gradual decrease in mitochondrial membrane potential was observed. HeLa cells showed significantly increased comet tail length (48.4 µm), indicating broken DNA strands. In silico studies exhibited that compound 1 binds to the active site of Polo-like kinase-1 and forms a stable complex. Conclusions: Racemolactone I was identified as potential anticancer agent, which can further be confirmed by in vivo investigations.